2020
DOI: 10.1016/j.etap.2020.103411
|View full text |Cite
|
Sign up to set email alerts
|

Two important controversial risk factors in SARS-CoV-2 infection: Obesity and smoking

Abstract: The effects of obesity and smoking in the coronavirus disease 2019 (COVID-19) pandemic remain controversial. Angiotensin converting enzyme 2 (ACE2), a component of the renin-angiotensin system (RAS), is the human cell receptor of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of COVID-19. ACE2 expression increases on lung alveolar epithelial cells and adipose tissue due to obesity, smoking and air pollution. A significant relationship exists between air pollution and SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
1
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(142 citation statements)
references
References 98 publications
8
116
1
17
Order By: Relevance
“…Tobacco smokers have a greater predisposition (1.4-fold) to develop severe symptoms of COVID-19. They often require admission to intensive care units (ICU), alongside concomitant mechanical ventilation; moreover, their death rate is approximately 2.4-fold compared to non-smokers ( Engin et al, 2020 ). Our results do not reveal any significant association between the estimated prevalence of the disease and being overweight.…”
Section: A Sociodemographic Characteristicsmentioning
confidence: 99%
“…Tobacco smokers have a greater predisposition (1.4-fold) to develop severe symptoms of COVID-19. They often require admission to intensive care units (ICU), alongside concomitant mechanical ventilation; moreover, their death rate is approximately 2.4-fold compared to non-smokers ( Engin et al, 2020 ). Our results do not reveal any significant association between the estimated prevalence of the disease and being overweight.…”
Section: A Sociodemographic Characteristicsmentioning
confidence: 99%
“…However, this may be countered by biomass burning for heating and cooking, which can make the indoor environmental conditions problematic along with outdoor air quality in valley regions prone to meteorological inversions (Thakur et al, 2020). Personal pollution exposure in the form of tobacco smoking may be a risk factor for greater COVID-19 rates (Alqahtani et al, 2020;Engin et al, 2020), but this has not been found in all studies (Rossato et al, 2020). Smoking increases airway epithelium expres-sion of ACE-2 (Leung et al, 2020;Zhang et al, 2020) and this may be further driven independently by airway nicotine exposure (Russo et al, 2020).…”
Section: Other Environmental Factorsmentioning
confidence: 99%
“…(Guan et al, 2020;Goyal et al, 2020;Young et al, 2020). Besides, a few retrospective cohort studies point out that other risk factors, including but not limited to older age (≥ 65 years old), smoking history, education level, and household income level, are likely to be associated with the clinical outcomes of COVID-19 (Engin et al, 2020;Liu et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%